Merchandise buying and management - Donnellan, John (Fairchild Books, 2014)
"The fourth edition of Merchandise Buying and Management has been updated to cover the most current information on merchandising and retailing. Written for college-level courses dealing with retail buying and the management for retail inventories, the text covers topics relevant to future buyers and store management personnel. The material is presented within the context of a contemporary retail environment-with examples from both fashion and non-fashion retailers-in which buyers often act as fiscal managers as well as product developers, and store managers play important roles in sales productivity and assortment planning. Retail technology is a theme that runs throughout the book, tied to topics such as space management, electronic data exchange, point-of-sale systems, and floor ready merchandise"--Provided by publisher.